Association between CD4 Cell Count and Blood Pressure and Its Variation with Body Mass Index Categories in HIV-Infected Patients - Christian Akem Dimala; Benjamin Momo Kadia; Ben-Lawrence Kemah; Maxime Tindong; Simeon-Pierre Choukem (International Journal of Hypertension)
The aim of this study was to establish whether an independent relationship exists between CD4 count and hypertension and if this relationship is modified or confounded by the body mass index (BMI). Methods. A secondary data analysis of a cross-sectional study on 200 HIV/AIDS patients at a referral hospital in Cameroon was conducted. Linear and logistic regression models were used as appropriate to explore the association between the variables of interest. Results. There was no linear association between log CD4 count and both systolic (p=0.200; r=0.12) and diastolic blood pressures (p=0.123; r=0.14), respectively. After adjusting for BMI, patients with CD4 count ≥ 350 cells/μl were more likely to have hypertension than those with CD4 count < 350 cells/μl (AOR: 2.50, 95% CI: 1.05–5.93, and p=0.032). There was no effect modification from BMI (test of homogeneity, p=0.721). There was no independent relationship between CD4 count and hypertension after controlling for age, sex, family history of hypertension, BMI-defined overweight, HAART use, and duration of HIV infection (AOR: 1.66, 95% CI: 0.48–5.71, and p=0.419). Conclusion. This study did not identify any independent relationship between CD4 count and hypertension. Large prospective studies are recommended to better explore this relationship between hypertension and CD4 count.